Extracellular nuclease from a thermophile, streptomyces thermonitrificans: production, purification and partial characterization of - double strand preferential - deoxyribonuclease activity - Patil, N. S.; Deshmukh, Satej S.; Shankar, V. (Process Biochemistry, 2005)
A thermophilic strain of Streptomyces themionitrificans produced high levels of extracellular nuclease (designated as nuclease Stn beta) when grown on nutrient broth glucose medium. Maximal nuclease activity (51 U ml(-1)) was obtained, in 40 h, when the culture was grown on modified NBG medium at 45 degreesC. The enzyme was purified to homogeneity with an overall recovery of 5.6% and a specific activity of 10,833. The relative molecular mass of the purified enzyme, determined by gel filtration, was 22.4 kDa and it showed an obligate requirement for Mn2+ for activity. The optimum pH and temperature of nuclease Stn beta were 8.0 and 45 degreesC, respectively. The enzyme was inhibited by Mg2+ CO2+, Cu2+, Zn2+ and Hg2+, inorganic phosphate, pyrophosphate, dithiothreitol, beta-mereaptoethanol, EDTA and NaCl. Nuclease Stn beta was stable to high concentrations of urea and organic solvents but susceptible to low concentrations of SDS and guanidine hydrochloride. Nuclease Stn beta is a multifunctional enzyme with substrate specificity in the order of dsDNA > ssDNA much greater than RNA. The end products of dsDNA hydrolysis were predominantly oligonucleotides (85-90%) and small amounts of 5' mononucleotides (10-15%) suggesting an endo mode of action. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Endonuclease; extracellular nuclease; production; Purification; Streptomyces thermonitrificans

Immobilized invertase - Kotwal, S. M.; Shankar, V. (Biotechnology Advances, 2009)
Invertase is a commercially important enzyme used for the hydrolysis of sucrose. The hydrolysis of sucrose yields an equimolar mixture of glucose and fructose, known as invert syrup, is widely used in food and beverage industries. This enzyme is also used for the manufacture of artificial honey, plasticizing agents used in cosmetics, pharmaceutical and paper industries as well as enzyme electrodes for the detection of sucrose. Immobilization of invertase and its biotechnological applications are reviewed. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Applications; Immobilization; Invert syrup; Saccharase